A study on the aspects of pharmacoepidemiology and pharmacohaemovigilance of ferrous ascorbate, ferrous fumarate, ferrous sulphate and ferric ammonium citrate, among the rural anaemic women, in the Indian spectrum - Hazra, Moumita (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Anaemia is a global health concern, associated with increased maternal and perinatal mortality, preterm delivery, low birth weight, extreme fatigue and impaired immune system; and controlled by oral haematinics; with a rise in haemoglobin concentration. The objective was to examine the various aspects of pharmacoepidemiology and pharmacohaemovigilance of oral haematinics, among the anaemic women population, in rural India. Methods: This was a multi-centre, retrospective, observational and analytical study of the hospital medical records of 250 anaemic patients, who were allocated into group A of 125 patients within 15-21 years and group B of 125 patients within 22-35 years. The patients were prescribed oral haematinics, containing 60 mg of elemental iron, thrice daily, with meals. The various aspects of pharmacoepidemiology and pharmacohaemovigilance of ferrous ascorbate, ferrous sulphate, ferrous fumarate and ferric ammonium citrate, including patients’ demographic characteristics, anaemic symptoms assessment, prescription patterns, and safety assessment, on 1st, 2nd, 3rd months and follow-up visits, were recorded and thoroughly analysed.. Results: In groups A and B, the demographic characteristics of the patients were comparable; ferrous ascorbate was the most commonly prescribed oral haematinic, followed by ferrous sulphate, ferrous fumarate and ferric ammonium citrate, which controlled mild to moderate iron deficiency anaemia, with a gradual significant rise in haemoglobin concentration, in the successive 3 months; and adverse effects were observed to be statistically non-significant in either group. Conclusions: The different aspects of pharmacoepidemiology and pharmacohaemovigilance in the study established that the oral haematinics were reasonably beneficial and safe among the anaemic women population, in rural India.